All-fiber figure-eight wavelength-tunable noise-like pulse lasers. (September 2021) - Lin, Jiaqiang; Dong, Zhipeng; Dong, Tianhao; Zhang, Yiming; Dai, Chuansheng; Yao, Peijun; Gu, Chun; Xu, Lixin
Highlights: The fiber loop mirror introduced into Er-doped oscillator acts as a comb filter. The central wavelength of the noise-like pulse is tunable. 53 nm continuous tuning range from 1547 nm to 1600 nm is obtained. Abstract: All-fiber wavelength-tunable fiber laser is a desirable light source architecture in many fields owing to their low cost, compactness and easy integration. However, most of them have independent filter elements and saturated absorption elements, which will undoubtedly increase the redundancy of laser. In this paper, we realize an all-fiber wavelength-tunable noise-like pulse (NLP) laser with the tunable central wavelength from 1547 nm to 1600 nm based on fiber loop mirror (FLM). The fiber loop (FLM) fused with two segments of polarization-maintaining fibers (PMF) acts as both a comb filter and a saturable absorber (SA). Such an all-fiber tunable NLP mode-locked laser wavelength at C-band (1530–1565 nm) and L-band (1565–1625 nm) is a potential choice for many practical applications.